Kaimo žmogaus paveikslas lietuvių literatūroje ir fotografijoje - Maskuliūnienė, Džiuljeta; Župerka, Kazimieras (Acta humanitarica academiae Saulensis, 2025)
The article reviews the image of a rural man in the Lithuanian literature and photography of the 20th century and contemporary times, explains how artistic images correlate with changes in the meaning and connotation of words designating a rural man. There is no doubt that the connotation of a person’s naming has one or another influence on his image in verbal and visual creation, and the paintings in turn support the different connotations of that naming. The village and a rural man have been depicted in Lithuanian literature since Kristijonas Donelaitis “Metai” (“Seasons”). The theme of rural aestheticization, making rural everyday life poetic, and the exaltation of the land and folk language comes from a romantic tradition. According to literary researchers, in the 19th century literature, the village was perceived as the only basis of Lithuanianness, and the rural man – as the equivalent of Lithuanianness. The village as a house of the spirit of the Lithuanian language is also raised in contemporary Lithuanian poetry and prose. It is no coincidence that the idea of Vaižgantas short story about the (in)ability to see and listen to the rich world of the rural human spirit “Akylasis būtų įspėjęs jame didžiulę inteligenciją, tik nebuvo kas įspėja” (A vigilant one would have noticed a great intelligence in it, only there was no one who could notice) can be seen in the novel by Laura Sintija Černiauskaitė “sielos šviesa, besismelkianti pro bukinantį skurdą ir nuovargį, – tokia menkutė, kad reikia mokytis ją atpažinti” (the light of the soul, seeping through the fading poverty and fatigue, is so small that one must learn to recognize it). In contemporary literature, quite a number of dark colours of the village and the rural man, sometimes obvious irony, ridicule are found. The texts of postmodern literature do not avoid depicting the village drastically, sarcastically, it is described by vulgar contemptuous neologisms (for example, “šūdkaimis” [shitty-village] by Aidas Jurašius). Thus, it can be stated that the depiction of the village and the rural man in contemporary Lithuanian literature corresponds to the diversifying connotation of the rural man in the current Lithuanian language and in the expression of other style texts. Rural photography in Lithuania has been for more than a hundred years; the rural photography of our country of the late 20th–early 21st century is also diverse. Some photographers, as typical of the Lithuanian photography tradition, refer more to the romanticization of rural man and rural life (e.g. Romualdas Rakauskas, Arūnas Baltėnas, Tadas Kazakevičius), others emphasize the diversity and polyphony of the village (brothers Mindaugas and Algimantas Černiauskai), and some photographers depict “the tired village”, the bottom of the village (Rimaldas Vikšraitis is especially prominent in this respect). The theme of saying farewell to agrarian culture, which has become entrenched in Lithuanian literature in the second half of the 20th century, is also being developed in photography (for example, a cycle “Tai, ko nebebus” (“What Will No Longer Be There”) by T. Kazakevičius). Photographers are resistant to spread of the negative, derogatory connotation of the rural man in the urban discourse, they rely on the cognition of the village, the feeling and reflection of its life, not on the stereotypes created by the urban culture.